Foreign experience of criminal law protection of personal data - Vabischevich, Vitaly V. (Journal of the Belarusian State University. Law, 2019)
The article deals with the foreign practice of bringing to criminal responsibility for criminal attacks on personal data. Foreign experience in criminal law protection of personal data shows that the introduction of criminal liability for direct violation of the legislation on personal data is an important element in the prevention of crimes in this area, as well as contributes to the effective implementation of legislation on personal data. Experience of the Russian Federation, Ukraine, Kazakhstan, Germany, Spain, Sweden, Switzerland, France, Great Britain is considered. The legal and regulatory framework in these countries is characterized by specific regulation of criminal liability for infringement of personal data. The author notes the presence of all the prerequisites and the need to establish appropriate criminal law protection of personal data and the addition of the Criminal code of the Republic of Belarus article, the direct object of protection of which will be established by the legislation of the order of circulation of personal data.